Rechnergestützte Versagensanalyse geklebter Verbindungen - Chudalla, Nick; Meschut, Gerson; Teutenberg, Dominik; Schneider, Miriam; Smart, Dominic (adhäsion KLEBEN & DICHTEN)

Methodenentwicklung zur Prognose des Crashverhaltens von widerstandspunktgeschweißten 3-Stahlblechverbindungen - Olfert, Viktoria; Schuster, Lilia; Bähr, Philipp; Hein, David; Meschut, Gerson; Sommer, Silke
Die aktuellen politischen und wirtschaftlichen Rahmenbedingungen zur Reduzierung der CO2-Emissionen sowie der Trend zur flächendeckenden Elektromobilität führen zu einer Vielzahl an neuen Herausforderungen für die Auslegung zukünftiger Fahrzeugkonzepte. Eine besondere Herausforderung ist das durch die Batterie ins Fahrzeug eingebrachte Zusatzgewicht. Hierdurch ergibt sich ein Konflikt zu der bestehenden Kundenerwartung nach einer hohen Reichweite. Durch den umfangreichen Einsatz von höchstfesten Stählen in dünnen Blechdicken im Karosseriebau soll die Reduzierung des Gesamtfahrzeuggewichts vorangetrieben werden. Vor allem im stahlintensiven Leichtbau ist das Widerstandspunktschweißen aufgrund des hohen Automatisierungsgrads, der Prozesssicherheit und der damit verbundenen Wirtschaftlichkeit das dominierende Fügeverfahren. Um Begrenzungen des Bauraums der Karosserie zu begegnen und um den Materialeinsatz im Leichtbau möglichst effizient zu gestalten, werden mehrschnittige Punktschweißverbindungen eingesetzt. Hieraus ergeben sich neue Herausforderungen für die Vorhersage des Trag- und Versagensverhaltens unter Crashbelastung. Dieser Beitrag stellt eine systematische Charakterisierung von 3-Blechverbindungen zur Auffindung von formelmäßigen, empirischen Zusammenhängen zwischen der Festigkeit der Verbindung und den Einflussgrößen vor. Nach der Identifikation geeigneter Einflussgrößen, wie zum Beispiel Blechfestigkeit, Blechanordnung, Blechdickenkombination sowie Belastungsart und Lasteinleitung, auf das Trag- und Versagensverhalten, werden numerische Simulationen durchgeführt, um Ursachen für auftretende Phänomene aus den experimentellen Ergebnissen aufzuklären. Weiterhin wird untersucht, inwieweit das Verhalten von 2-Blechverbindungen auf 3-Blechverbindungen übertragbar ist. Die gefundenen Zusammenhänge sollen schnelle und kostengünstige Abschätzungen über die Festigkeit von 3-Blechbverbindungen ermöglichen. Darüber hinaus werden Ersatzmodelle für die Crashsimulation von 3-Blechverbindungen entwickelt, die recheneffizient für die Sicherheitsbewertung von großen, geschweißten Bauteilen eingesetzt werden können. Dabei sollen insbesondere die Einflüsse des Lastangriffs an jeweils einer oder beiden Fügebenen auf die Festigkeit und Energieabsorption unter verschiedenen Belastungen wie Zug, Scherung sowie Biegung abbildbar sein.

Extracting perfect GHZ states from imperfect weighted graph states via entanglement concentration - Frantzeskakis, Rafail; Liu, Chenxu; Raissi, Zahra; Barnes, Edwin; Economou, Sophia E. (Physical Review Research)

Die Stimmen der Eroberten bei Ermoldus Nigellus. Eine Mahnung an Ludwig den Frommen und Pippin von Aquitanien - Foerster, Anne (Eroberte im Mittelalter: Umbruchssituationen erleben, bewältigen, gestalten)

Charles Perraults 'Le Siècle de Louis le Grand' oder die Erfindung von Traditionen - Steigerwald, Jörn (Zeiten bezeichnen. Frühneuzeitliche Epochenbegriffe: europäische Geschichte und globale Gegenwart)

Efficient gradient enhancements for plasticity with ductile damage in the logarithmic strain space - Friedlein, Johannes; Mergheim, Julia; Steinmann, Paul (European Journal of Mechanics - A/Solids)
We contrast different gradient-enhancements for plasticity-damage material models in the logarithmic strain space and compare them to reference models based on multiplicative plasticity. The models being compared include plasticity - gradient-damage, where the gradient-enhancement is applied on the local damage variable, and gradient-plasticity - damage with a gradient-enhanced plastic hardening variable. Thereby, gradient-plasticity proved to be able to simultaneously regularise plastic and ductile (plasticity-driven) damage localisation as confirmed by numerical localisation analyses. This appears to be especially advantageous for logarithmic strain space plasticity-damage, because of the observed plastic localisation even for the case of plasticity with hardening. Even though gradient-plasticity appears to be numerically more demanding, two numerical examples indicate a good robustness and mesh objectivity in the softening regime. Moreover, the internal length for plasticity is able to adjust the damage zone width, similarly to gradient-damage, however ensuring a priori that damage takes place exclusively inside the plastic zone.
Keywords: Finite plasticity; Logarithmic strain space; Ductile damage; Gradient-enhancement; Gradient-plasticity; Gradient-damage; Loss of ellipticity

LoRa Transceiver for Load Monitoring and Control System in Microgrids - Mwammenywa, Ibrahim; Petrov, Dmitry; Holle, Philipp; Hilleringmann, Ulrich (2022 International Conference on Engineering and Emerging Technologies (ICEET))

Polarization dynamics in spin‐VCSELs with integrated surface grating for high birefringence splitting - Lindemann, Markus; Jung, Natalie; Gerhardt, Nils Christopher; Hofmann, Martin R.; Manrique‐Nieto, Nicolas; Pusch, Tobias; Michalzik, Rainer (Electronics letters)

Coupled Aperture VCSELs Suitable for 100 GHz Intensity Modulation - Lindemann, Markus; Gerhardt, Nils C.; Hofmann, Martin R.; Ledentsov, N.; Shchukin, V. A.; Ledentsov, N. N.; Makarov, O. Yu.; Chorchos, L.; Turkiewicz, J. P. (2023 23rd International Conference on Transparent Optical Networks (ICTON))

Analysing the API learning process through the use of eye tracking - Sparmann, Sören; Schulte, Carsten (2023 Symposium on Eye Tracking Research and Applications)

Modelling of Composite Manufacturing Processes Incorporating Large Fibre Deformations and Process Parameter Interactions - Example Braiding - Gröger, Benjamin; Gerritzen, Johannes; Eckardt, Simon; Gelencsér, Anton; Kunze, Eckart; Hornig, Andreas; Protz, Richard; Gude, Maik

Controlled Rivet Deformation During Self-piercing Riveting Through a Tailored Strength Distribution Within the Rivet Material - Uhe, Benedikt; Kuball, Clara-Maria; Merklein, Marion; Meschut, Gerson (Proceedings of the 14th International Conference on the Technology of Plasticity - Current Trends in the Technology of Plasticity.)
The use of stainless steel with high strain hardening as material for self-piercing rivets is a promising approach to shorten the manufacturing process. Due to the corrosion resistance of the material and the achieved high strength within the forming process, the heat treatment and the coating can be omitted. As the strength within the rivet material is achieved by cold forming, the strength distribution within the rivet remains intact after the manufacturing process. The aim of the contribution presented is the exploitation of the potential of this strength distribution to improve the performance of the self-piercing rivets. Therefore, the scope of the examination is on the analysis of the influence of the local strength on the deformation behaviour of the rivet during joining. While it is unfeasible to manufacture rivets with any desired strength distribution, numerical simulation offers an efficient opportunity to study the effects of varying local strengths. By using a definable true strain distribution within the rivet as presetting for the simulation, different strength distributions can be modelled. Through the simulation of the joining process, the deformation behaviour of the rivet can be examined. Based on the insights of this analysis, a strength distribution is created that supports the joining of challenging material combinations consisting of high strength steel and aluminium. Finally, the approach is verified by experimental joining tests.

Increased Sustainability in Fastener Production with the Example of Self-Piercing Rivets - Uhe, Benedikt; Kuball, Clara-Maria; Merklein, Marion; Meschut, Gerson (Journal of Manufacturing and Materials Processing)
The sustainability of the manufacturing industry is of special importance to increase the protection of the environment. The production of fasteners like self-piercing rivets, however, is costly, time-consuming and energy-intensive. The heat treatment and the coating, which are mandatory in conventional self-piercing rivets to achieve adequate strength, ductility and corrosion resistance, are especially crucial in this respect. Within this paper, an approach for an increase in the sustainability in fastener production is presented. The use of alternative, high strain hardening stainless steels as rivet material enables a shortening of the process chain, because post treatment of the rivets after they are formed can be omitted. As the change in rivet material and processing causes some issues along the process chain, the focus of this paper is on the holistic evaluation of the challenges within the forming of high strain hardening steel and the impact of the changed rivet properties on the joining result.
Keywords: Industrial and Manufacturing Engineering; Mechanical Engineering; Mechanics of Materials

Approach for a sustainable process chain in manufacturing of fasteners for mechanical joining - Uhe, Benedikt; Kuball, Clara-Maria; Merklein, Marion; Meschut, Gerson
With regard to environmental protection, the sustainability of production processes is decisive. Mechanical joining technologies like self-piercing riveting are of special importance with regard to realising lightweight constructions in the automotive industry. However, the production of self-piercing rivets is costly, time-consuming and energy-intensive, as the rivets conventionally must be heat treated and coated in order to ensure an adequate strength, ductility and corrosion resistance. Within this paper, it is shown by the example of a newly established rivet manufacturing process how the sustainability of fastener production can be increased. The general approach in this context is the use of alternative, high strain hardening stainless steels as rivet material, which allows the omission of the post treatment of the rivets after forming. The shortening of the process chain enables a more sustainable rivet production. Thus, not only the energy consumption is reduced, but also costs, which is why the novel manufacturing process is also of interest from an economic point of view.

Increased Sustainability in Fastener Production with the Example of Self-Piercing Rivets - Uhe, Benedikt; Kuball, Clara-Maria; Merklein, Marion; Meschut, Gerson (Journal of Manufacturing and Materials Processing)
The sustainability of the manufacturing industry is of special importance to increase the protection of the environment. The production of fasteners like self-piercing rivets, however, is costly, time-consuming and energy-intensive. The heat treatment and the coating, which are mandatory in conventional self-piercing rivets to achieve adequate strength, ductility and corrosion resistance, are especially crucial in this respect. Within this paper, an approach for an increase in the sustainability in fastener production is presented. The use of alternative, high strain hardening stainless steels as rivet material enables a shortening of the process chain, because post treatment of the rivets after they are formed can be omitted. As the change in rivet material and processing causes some issues along the process chain, the focus of this paper is on the holistic evaluation of the challenges within the forming of high strain hardening steel and the impact of the changed rivet properties on the joining result.

Influence of Temperature and Pre-Stress on the Piezoelectric Material Behavior of Ring-Shaped Ceramics - Scheidemann, Claus; Hemsel, Tobias; Friesen, Olga; Claes, Leander; Sextro, Walter

Note: Ungenügend – Ernährung in der Schule - Dankers, Rhea (UGB Forum)

Vegetarische/vegane Alternativen zu Fisch und Meeresfrüchten - Teil 1 - Knies, Jana Maria (Ernährungs Umschau)

Vegetarische/vegane Alternativen zu Fisch und Meeresfrüchten – Teil 2 - Knies, Jana Maria (Ernährungs Umschau)

Does listener gaze in face-to-face interaction follow the Entropy Rate Constancy principle: An empirical study - Wang, Yu; Buschmeier, Hendrik (Findings of the Association for Computational Linguistics: EMNLP 2023)
It is generally assumed that language (written and spoken) follows the entropy rate constancy (ERC) principle, which states that the information density of a text is constant over time. Recently, this has also been found for nonverbal gestures used in monologue, but it is still unclear whether the ERC principle also applies to listeners' nonverbal signals. We focus on listeners' gaze behaviour extracted from video-recorded conversations and trained a transformer-based neural sequence model to process the gaze data of the dialogues and compute its information density. We also compute the information density of the corresponding speech using a pre-trained language model. Our results show (1) that listeners' gaze behaviour in dialogues roughly follows the ERC principle, as well as (2) a congruence between information density of speech and listeners' gaze behaviour.